A Critical Review of IELTS Speaking Test - Rita Seroja Ginting; Ahmad Amin Dalimunte; Muhammad Dalimunte; Eka Yuni Kurniati; Devika Adelita (JL3T (Journal of Linguistics, Literature and Language Teaching))
The present study on content analysis attempts to give detailed examinations of the IELTS Speaking Test. It provides an overview of the aim of tests, as well as their reliability and validity, along with a discussion of language testing during the previous three decades. The merits and limitations of the IELTS Speaking Test were investigated, with an emphasis placed on exam scenarios. Validity, reliability, and application served as the evaluation criteria for this study. The IELTS speaking test is accurate and reliable in general; however, there are a few contentious aspects that may have an effect on the test's reliability and validity. These aspects were investigated and described in this paper. In general, the IELTS speaking test is accurate and reliable. There, the following potential proposals were made: A double-marking technique, a video conference delivery, and an intervention are all examples. The IELTS Speaking Test is one specialized component that is administered in a distinct place from the IELTS Listening, Reading, and Writing tests on the same or a different day. By using the face-to-face method, the examiner only needs to do an evaluation of the candidate's performance once, and the entire process is recorded so that there is a record in case something goes wrong. A few weeks after the test, candidates will receive the results online and by mail. Subjective factors like candidate preferences and marker performance will have a significant impact on the entire testing process and evaluation findings.